Differentiation Between Chaenomelis Fructus and its Common Adulterant, Guangpi Mugua. (19th August 2021) - Lyu, Mengying; Liu, Yang; Qiu, Yixing; Yang, Shuai; Yuan, Hanwen; Wang, Wei
Abstract: Background: The dried fruit of Chaenomeles speciosa, known as Chaenomelis Fructus or Zhoupi Mugua, is a type of traditional Chinese medicine (TCM) that is widely used to treat many diseases. Guangpi Mugua, the dried fruit of the Chaenomeles sinensis, is its most commonly known adulterant. Objective: To establish a robust approach for the quality control and identification of Chaenomelis Fructus. Method: Thin-layer chromatography (TLC) was optimized and used to discriminate Chaenomelis Fructus from Guangpi Mugua. High-performance liquid chromatography (HPLC) combined with fingerprint analysis and partial least-squares (PLS) discrimination analysis (DA) was employed to study the chemical differences between Chaenomelis Fructus and Guangpi Mugua. The single standard to determine multi-components (SSDMC) method, with credible precision, repeatability, stability, and durability, was developed for quantitative analysis of the abundant markers. Results: The developed TLC and HPLC methods were effective in the authentication of Chaenomelis Fructus. Moreover, oleanolic acid, ursolic acid, pomolic acid, corosolic acid, 3- O -acetylpomolic acid, and one unknown compound were identified to be critical markers for the discrimination of Chaenomelis Fructus from Guangpi Mugua. Conclusion: Adulteration has always been a challenge in the development of TCM. This study presents useful insights that may help solve the problem of adulteration during the preparation of Chaenomelis Fructus. Highlights: The present study provides a systematic method for the quality control of Chaenomelis Fructus. This is therefore the first step towards solving the problem of adulteration to improve the clinical safety and effectiveness of Chaenomelis Fructus.